THE RELATIONSHIP BETWEEN STUDENTS PERCEPTION WITH COVID-19 PREVENTION BEHAVIORS ON EDI MANCORO BOARDING SCHOOL OF SEMARANG - Nur Dina Nofita Krismawati; Priyadi Nugraha Prabamurti; Aditya Kusumawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Islamic Boarding School has a high risk of COVID-19 transmission. The COVID-19 transmission occurs due to the lack of students’ effort of COVID-19 prevention and does not disipline in following health protocols on islamic boarding school. This study analyzes the relationship between students’ perception with COVID-19 prevention behaviors on Edi Mancoro Boarding School of Semarang.This study used observational descriptive with cross-sectional study. The population of this study was 310 students and 75 students became participants and were determined based on purposive sampling method. Data was collected by fitting out questionnaires and was analyzed using Chi-square test. The analysis showed that 58,7% of respondents had well-implemented preventive behaviors of COVID-19. The mean gender was woman (60%), age of participants was more than equal to 20 years (66,7%). For most of them, the length of stay in an islamic boarding school was more than equal to 2 years (68%). Students had good knowledge (69,3%), had positively perceived susceptibility (58,7%), had positively perceived severity (50,7%), had positively benefits (77,3%) had positively perceived barrier (65,3%), had positive self-efficacy (93,3%) and had positive cues to action (64%). The result relationship test showed that gender (p=0,002), knowledge (p=0,022), perceived susceptibility (p=0,014), perceived severity (p=0,002) and perceived barriers (p=0,002) were releted with preventive behaviors of COVID-19. Unrelated factors are age, alllowance, the length of stay in islamic boarding school, perceived benefits, cues to action and self-efficacy with COVID-19 prevention behavior on Edi Mancoro boarding school of Semarang. Keyword : Islamic Boarding School, COVID-19 Prevention Behavior